The Mediating Effect of Job Satisfaction on Teacher Performance Based on Work Motivation and Organizational Culture - Stefanus Roi Rosena; Soedjono (Optima Science, 2024)
This study aims to examine the influence of motivation and Organizational Culture on Employee Performance through Job Satisfaction as mediation. The population of this study was all civil servants at SD Negeri Madyopuro, Malang City. The sampling technique used in this study was saturated samples, with a total of 37 respondents. The analytical technique used is a structural equation model (Structural Equation Modeling - SEM) Based variance component based SEM, yang dikenal dengan Partial Least Square (PLS). The results of this study are that 1) Motivation has a positive and significant effect on the Job Satisfaction of civil servant teachers at SDN Madyopuro Malang City, 2) Organizational Culture has a positive and significant effect on the Job Satisfaction of civil servant teachers at SDN Madyopuro Malang City, 3) Motivation has a positive and significant effect on the Performance of civil servant teachers at SDN Madyopuro Malang City, 4) Organizational Culture has a positive and significant effect on the Performance of civil servant teachers at SDN Madyopuro Malang City, 5) Job Satisfaction has a positive and significant effect on the performance of civil servant teachers at SDN Madyopuro Malang City, 6) Job Satisfaction has a mediating influence between Motivation Variables and Teacher Performance Variables, 7) Job Satisfaction has a mediating influence between Organizational Culture Variables and Teacher Performance Variables.